Buoyant (leg-sinking) torque in able-bodied swimmers and swimmers with impaired leg functions - Payton, C. J.; Reid, A. K. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
A swimmer's ability to float statically in a horizontal position is determined largely by the turning effect resulting from their body weight and buoyancy forces. This is termed the buoyant torque. As a body's weight acts through its centre of mass (CaM) and the buoyancy force acts though its centre of buoyancy (CoB), the distance between these two centres will determine the static floating position of an individual (Gagnon & Montpetit 1981; Mclean & Hinrichs 1998). In static floating, the CoB is generally closer to the head than the CoM. Consequently, the buoyant torque acts to sink the legs. Due to sex differences in body mass distribution, males generally experience a greater buoyant torque than females, resulting in a greater tendency for their legs to sink (Gagnon & Montpetit 1981; Mclean and Hinrichs 1998). Lung volume and arm position both influence buoyant torque (Mclean & Hinrichs 2000). An increase in lung volume, by breathing in, increases the volume of the upper body without increasing its mass. This moves the CoB cranially with little or no effect on the CaM position. Consequently, the momentarm of the buoyancy force increases thus increasing the buoyant torque. When one or both arms are extended overhead, the CoB and CoM both shift cranially, but the movement of the CaM is greater. This brings the weight and buoyancy forces closer together thus reducing the buoyant torque. Drag is an important determinant of swimming performance. One of the key factors influencing drag is the projected frontal area of the swimmer which, in turn, is affected by the horizontal alignment of the body in the water (Kjendlie, Stallman & Stray-Gundersen 2004). Para-swimmers who are unable to kick, due to impaired leg function, may be disadvantaged over those who compete in the same class but who are able to kick. Not only are they unable to use a leg-kick to help maintain horizontal alignment, but their body mass distribution, due to atrophied lower extremities, may differ from that of non-impaired swimmers and so, consequently, may the buoyant (leg-sinking) torque they experience. This study's aim was to establish whether the buoyant torque differs between swimmers with impaired leg function and able bodied swimmers.